The Effect of External Sourcing on The Financial Performance of Manufacturing Companies Listed in Indonesia Stock Exchange (BEI) - Risya Maulida Septiana; Noer Azam Achsani; Tony Irawan (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
There were differences in research results of several previous studies which examined the relationship between external sourcing and corporate financial performances. Those results indicated that external sourcing could have a positive, negative, or no effect on the financial performance of the company. There was numerous literature stated that external sourcing was a strategy to minimize costs which could reduce production and procurement costs, thus becoming a strategy considered by the top management to improve the company performance. This study analyzed the external sourcing effects on financial performance (ROA) of manufacturing company listed in Indonesia Stock Exchange (BEI). Total population of manufacturing companies listed in the Indonesia Stock Exchange from 2012-2016 was as many as 132 companies, but there were only 70 companies that met the criteria to be the object of the research. The manufacturing company used three industry sectors namely basic and chemical industry, consumer goods industry, and miscellaneous industry as the research objects. Using panel data regression, the research results indicated that external sourcing strategy had a significant and negative effect on ROA. Negative effects resulting from purchases on external parties (external sourcing) were caused by the high cost of sales exceeded the company revenue. Therefore, the company should pay attention to the level of purchases made, namely purchases to the third party on raw materials and goods in the process to have the level of purchases at an optimal point in order to generate profits for the company.Keywords: external sourcing, financial performance, panel data, manufacturing company